El “desarrollador-plataforma”, nuevo actor de la división del trabajo inmobiliario financiarizado en México - David, Louise (El Colegio de México A.C., 2017)
Several transnational financial investors invest in Mexican real estate markets, leading to its “financialization,” in other words, markets are transformed by the growing influence of strategies and financial evaluation tools. These financial investors promote the idea that real estate developers should change the economic model to become “platform developers”: by suggesting investment opportunities and offering project development and management services. Thus, financial investors are promoting a new division of real estate labor where they can monopolize and control capital investment.